PENGARUH TATA KELOLA PERUSAHAAN, STRUKTUR KEPEMILIKAN, DAN DIREKSI WANITA PADA MANAJEMEN LABA - JULIEYANTI LIEBRIDA; MARIA MARIA (E-Jurnal Akuntansi TSM, 2022)
This study aims to obtain empirical evidence and analyze factors that affecting earnings management. The independent variables tested in this study were board size, independent audit committee, managerial ownership, firm size, leverage, firm growth, institutional ownership, and female directors. This research uses manufacturing company listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020 and the number of research samples is 199 companies with a total of 357 research dat.a The results of this research are firm growth has an effect on earnings management.